ᵃʳᶜʰPbWO₄ with improved optical parameters from archaeological lead - Yakubovskaya, A.G.; Tupitsyna, I.A.; Dubovik, A.M. (Вопросы атомной науки и техники, 2022)
Technological principles of manufacturing a lead tungstate crystal from archaeological lead for use in low-background experiments to search for rare events are presented. The influence of the conditions for obtaining single crystals of ᵃʳᶜʰPbWO₄ on the photochromic effect in single crystals is investigated. By minimizing deviations from the stoichiometric composition, it was possible to improve the optical parameters of the lead tungstate single crystal. Single crystals with improved optical parameters have been obtained using double crystallization and the introduction of an excess of ᵃʳᶜʰPbO, which makes it possible to consistently influence various defects in crystals of ᵃʳᶜʰPbWO₄.